Availability and provision of emergency obstetric care under a public–private partnership in three districts of Gujarat, India: lessons for Universal Health Coverage. Issue 1 (13th April 2016) - Iyer, V; Sidney, K; Mehta, R; Mavalankar, D
Abstract : Objective: The state of Gujarat in India (population 60 million) has implemented a public–private partnership (PPP) with private obstetricians called the Chiranjeevi Yojana (CY) since 2006. This study investigated the adequacy of basic and comprehensive emergency obstetric care (BEmOC and CEmOC) services through the public and private sectors with reference to the United Nations (UN) guidelines. Design: A cross-sectional facility survey was conducted in three districts. Results: A total of 300 facilities, 151 public and 149 private, had provided obstetric services to a total of 53 896 births in the past 6 months. Nearly half, 135 facilities (104 public and 31 private), individually reported <10 births per month (low load), and, as a group, reported only 4% of all births in the past 6 months. The remaining 165 high-load facilities consisted of 23 (3 public; 20 private) full CEmOC, 66 (1; 65) 'potential' CEmOC, 12 (3; 9) BEmOC and 57 (40; 17) non-EmOC facilities. All the three districts exceeded the UN recommendation for EmOC availability by 3.3 to 11.3 times. Free provision, through both public and PPP facilities, ranged from 1.42 to 3.43. The actual performance was nearly double the recommendation for CEmOC but inadequate for BEmOC. Conclusions: Public sector EmOC availability and provision is negligible. Private sector availability is well beyond the recommended UN norms. The CY programme has resulted in increased availability and provision of EmOC services. However, the overall provision of EmOC is compromised due to the poor performance of BEmOC functions and clustering of private facilities in towns.